PROMOTIING LEARNER AUTONOMY: TEACHERS, APPLICATION IN MANAGING CLASS (A STUDY AT SMA ADABIAH, PADANG) - Mulyani, Putri; Sani, Riny D. (TELL - US JOURNAL, 2017)
This study aims to look how the teachers applied the strategies used to promote learner autonomy in the classroom. The research design was descriptive using qualitative approach. Source of the data from this study is an English teacher in high school Adabiah Padang totaling three teachers. In collecting the data, the researcher used observation checklist, field note and video recorder. When observed by using a checklist and field notes, researchers looked at all the activities of teachers and checklist based on indicators of the strategies to promote leaner autonomy in the classroom. Observations were also supported with video recording in order to help the researcher in the data process. There are six indicators used in this study, namely leaner goals, focusing on student's independence from the teacher, providing opportunities for the students to learn from each other, leaner strategy, providing opportunities for self-peer correction and reflection on learning. After analyzing or data process obtained from the use of such instruments, the researcher found that only two of the six indicators are often used by two the teachers from the three teachers that observed were providing opportunities from the student's to learn from each other and providing self-peer opportunities for correction. The percentage of promoting leaner autonomy: teachers' application in managing class at SMA Adabiah Padang, for teacher A is low level (33,3%), for teacher B is low level (33 ,3%) and for teacher C is very low (1 6,6%).